2016
DOI: 10.1016/j.ejbas.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation structure and soil characteristics of five common geophytes in desert of Egypt

Abstract: Geophytes are kind of plants having the capability to survive under arid environmental conditions; parts of their bodies are dormant fleshy underground as bulbs, corms, tubers or rhizomes. The present study was designed to throw light on the ecological features of five representative geophytes, namely, Cyperus capitatus, Cyperus conglomeratus, Elymus farctus, Lasiurus scindicus and Panicum turgidum. The soil characteristics and the associated species of these geophytes are described in their natural habitats o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…This result agrees with most of related studies Barakat et al, 2014;El-Amier, 2016). Saharo-Arabian and Mediterranean chorotypes represented 22.6% of the recorded flora.…”
Section: Discussionsupporting
confidence: 82%
“…This result agrees with most of related studies Barakat et al, 2014;El-Amier, 2016). Saharo-Arabian and Mediterranean chorotypes represented 22.6% of the recorded flora.…”
Section: Discussionsupporting
confidence: 82%
“…Also, Abd reported that, about 31.15%, 28% and 18% of therophytes, hemicryptophytes and chamaephytes are represented in the vegetation of Qift-Qusier roadside, respectively, The prevalence of the Mediterranean chorotype of the listed flora in the study area reflects the Mediterranean climate of studied area. This result agrees with most of related studies (Salama et al, 2013;Barakat et al, 2014;El-Amier, 2016;El-Amier and Abd El-Gawad, 2017). Saharo-Sindian and Mediterranean chorotypes accounted for 30.96% of recorded plants.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with the results of Abd El-Galil [ 75 ], who studied the floristic composition of Wadi Al-Assiuty, Eastern Desert, Egypt. In arid and semi-arid regions, chamaephyte and therophyte were found to be the most common life-forms [ 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%